Management of Anesthesia in Mandibular Tumors with Difficult Airway - Marthendro, Triade; Irawan, Dino (Journal La Medihealtico, 2024)
A 39 year old female patient with a diagnosis of mandibular tumor underwent mandibulectomy and Free Fibular Flap reconstruction. Preoperative evaluation is carried out on patients, namely by carrying out anamnesis, physical examination and supporting examinations to determine the problem and conclude the patient's physical status. The patient's physical status is ASA III. The patient was intubated awake with a video laryngoscope. After that, sedation and muscle relaxants are given. The operation lasted 10 hours with stable hemodynamics. Post-operatively, patients are treated in the ICU, vital signs are observed and post-operative pain is managed. A closed study conducted by the Professional Committee of the American Society of Anesthesiologists (ASA) revealed that the risks and serious complications of anesthesia are most often closely related to airway management problems. Success in dealing with complications depends on early detection of symptoms and corrective action to prevent the situation from getting worse. In this patient, airway management was based on the Difficult Airway Algorithm.